Effects of core strength training on maximal trunk muscle strength and cycling economy in female mountain bikers - Blechschmied, R.; Strahler, J.; Granacher, U. (Sports Medicine - Open, 2026)
Background In cross-country mountain biking (MTB), performance is primarily determined by aerobic capacity. However, shortened race durations from 150 to 80 min increased the relevance of anaerobic capacity, muscle strength, and power. Adequate levels of trunk muscle strength (TMS) enable force transfer between lower and upper extremities during starts, inclines, and finishes. Cycling economy (CE) may benefit from TMS training. This study examined the effects of TMS training on TMS, TMS endurance, and CE in MTB athletes.